Methamphetamine abuse impairs sequential working memory - Yao, Wang; Zhang, Hao; Li, Shuaiqi; Song, Sensen; Ye, Zheng; Zhou, Xiaolin (Frontiers in Psychiatry, 2024)
The ability to maintain and manipulate sequential information in working memory, referred to as sequential working memory, plays a vital role in our daily life. While research has shown that methamphetamine abuse affects the neural substrates and the overall functioning of working memory, its specific impact on sequential working memory remains unclear. In this study, we asked 62 abstinent methamphetamine-dependent participants and 59 control participants to complete a digit ordering task in which they saw four digits one-by-one over time and subsequently rearranged them in ascending order. The four digits were presented either randomly in the experimental condition or in ascending order in the control condition. Results show that methamphetamine-dependent participants performed worse than the controls in the experimental condition in which sequential working memory was needed to complete the task, but not in the control condition in which only short-term memory was needed. This finding demonstrates that methamphetamine abuse impairs sequential working memory.